Why to these rocks : 50 years of poems from the Community of Writers - Alvarez, Lisa; Hass, Robert; Community of Writers (Berkeley, California : Heyday ; Nevada City, California : Community of Writers, 2021)
"The Community of Writers (formerly Squaw Valley Writers' Conference) celebrates fifty years of its annual summer poetry workshop in Olympic Valley, California, with this collection of one hundred and forty poems first composed there"--
Keywords: American poetry -- 21st century; American poetry -- 20th century